Learning Angular - Third Edition - Bampakos, Aristeidis (Packt Publishing, 2020)
Uncover Angular's potential for creating enterprise web applications--from setting up the environment to deployment--with the help of expert guidance, step-by-step explanations, and hands-on exercises Key Features Learn the fundamentals of Angular to build web applications using TypeScript Explore the basics of Angular development, from components and templates to forms and services Discover best practices for building, packaging, and testing Angular applications Book Description Angular, loved by millions of web developers around the world, continues to be one of the top JavaScript frameworks thanks to its regular updates and new features that enable fast, cross-platform, and secure frontend web development. With Angular, you can achieve high performance using the latest web techniques and extensive integration with web tools and integrated development environments (IDEs). Updated to Angular 10, this third edition of the Learning Angular book covers new features and modern web development practices to address the current frontend web development landscape. If you are new to Angular, this book will give you a comprehensive introduction to help you get you up and running in no time. You'll learn how to develop apps by harnessing the power of the Angular command-line interface (CLI), write unit tests, style your apps by following the Material Design guidelines, and finally deploy them to a hosting provider. The book is especially useful for beginners to get to grips with the bare bones of the framework needed to start developing Angular apps. By the end of this book, you'll not only be able to create Angular applications with TypeScript from scratch but also enhance your coding skills with best practices. What you will learn Use the Angular CLI to scaffold, build, and deploy a new Angular application Build components, the basic building blocks of an Angular application Discover techniques to make Angular components interact with each other Understand the different types of templates supported by Angular Create HTTP data services to access APIs and provide data to components Enhance your application's UX with Angular Material Apply best practices and coding conventions to your large-scale web development projects Who this book is for The Angular TypeScript book is for JavaScript and full-stack developers who want to enter the world of frontend development with Angular or migrate to the Angular framework to build professional web applications. Famil...
Title from content provider
Keywords: Application software -- Development; TypeScript (Computer program language); Web applications -- Development; Web applications -- Programming; Web site development; Web sites -- Design; Logiciels d'application; Développement; TypeScript (Langage de programmation); Applications Web; Développement; Applications Web; Programmation; Sites Web; Développement; Sites Web; Conception; Web sites; Design; Application software; Development